Les connaissances comme ressources du développement régional - Roland Scherer; Klaus-Dieter Schnell (Revue de Géographie Alpine)
The economic and social development of regions is facing new challenges nowadays. European integration and extension, as well as the globalised climate/structure with regard to economics and decision-making, and globalised economic and decisionrelated coherencies are bringing about major changes. Regions as business locations are competing more and more for mobile and immobile resources. Regions need to understand and utilise their “knowledge” as a development resource in order to be able to develop themselves. The resource of “knowledge” is also becoming increasingly significant in regional politics. The “new regional policy” in Switzerland is treading new ground with the establishment of a “regional development knowledge management system” and considerable amounts of public funding are being invested in this scheme.